Supraglottic airway devices for administration of surfactant to newborn infants with respiratory distress syndrome: a narrative review. Issue 3 (28th September 2020) - Roberts, Calum T; Manley, Brett James; O'Shea, Joyce E; Stark, Michael; Andersen, Chad; Davis, Peter G; Buckmaster, Adam
Abstract : Surfactant is an effective treatment for respiratory distress syndrome, being particularly important for infants in whom continuous positive airway pressure (CPAP) provides insufficient support. Supraglottic airway devices present an attractive option for surfactant delivery, particularly as an alternative to methods dependent on direct laryngoscopy, a procedural skill that is both difficult to learn and in which to maintain competence. Published studies provide encouraging data that surfactant administration by supraglottic airway device can be performed with a high rate of success and may reduce the need for subsequent intubation compared with either continued CPAP or surfactant administration via endotracheal tube. However, existing randomised controlled trials (RCTs) are heterogeneous in design and include just over 350 infants in total. To date, all RCT evidence has been generated in tertiary units, whereas the greatest potential for benefit from the use of these devices is likely to be in non-tertiary settings. Future research should investigate choice and utility of device in addition to safety and effectiveness of procedure. Importantly, studies conducted in non-tertiary settings should evaluate feasibility, meaningful clinical outcomes and the impact that this approach might have on infants and their families. Supraglottic airway devices may represent a simple and effective mode of surfactant administration that can be widely used by a variety of clinicians. However, further well-designed RCTs are required to determine their role, safety and effectiveness in both tertiary and non-tertiary settings before introduction into routine clinical practice.